In-situ TEM observation of the evolution of helium bubbles & dislocation loops and their interaction in Pd during He+ irradiation. (10th October 2021) - Han, Qing; Li, Yipeng; Ran, Guang; Liu, Xinyi; Wu, Lu; Chen, Yang; Chen, Piheng; Ye, Xiaoqiu; Ding, Yifan; Wu, Xiaoyong
Graphical abstract: Highlights: The evolution of bubbles & dislocation loops and their interaction in Pd during He + irradiation were in-situ studied. Irradiation induced the formation of perfect loops and faulted loops, but faulted loops were the majority at the low dose. Sample thickness obviously affected the ratio of faulted loop variants, the size and number density of loops. Loop size and loop volume number density had different evolution trends with the increase of irradiation dose. The bubble mainly appeared in the dislocation loops at low irradiation dose. Abstract: The microstructural evolution of purity Pd under 30 keV He + irradiation at 573 K was investigated by in-situ transmission electron microscopy. The nucleation, growth, merging, annihilation, size change, number density variation, and types of dislocation loops were analyzed under the influence of irradiation fluence and sample thickness. Both perfect dislocation loops with b = 1/2 < 110> and faulted dislocation loops with b = 1/3 < 111> were formed. However, at low irradiation fluence, most of the loops were 1/3 < 111> loops. The thickness of TEM foil obviously affected the ratio of 1/3 < 111> loop variants, the size and number density of dislocation loops, and the characteristics of bubble-loop complexes. With the increase of irradiation fluence, the size of dislocation loops increased, but loop volume number density remained almost constant until dislocation loops merged and evolved into dislocation network. There was an obvious interaction between dislocation loops and bubbles, indicating that 1/3 < 111> loop was first formed at the initial stage of irradiation, and when the loop grew to a certain size, obvious helium bubbles appeared inside its region.